PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS TERHADAP TAX AVOIDANCE YANG DIMODERASI UKURAN PERUSAHAAN - Angella, Angella; Widyasari , Widyasari; adang, Ferry (Jurnal Paradigma Akuntansi, 2025)
This study aims to determine the effect of the relationship between profitability, leverage, and liquidity on tax avoidance and is moderated by firm size in property and real estate sector companies listed on the Indonesia Stock Exchange in 2019-2021. This research uses secondary data. The method used to select the sample was purposive sampling and the valid data were 14 companies. The data processing technique used was multiple regression analysis and moderated regression analysis assisted by the Eviews 12 program. The result of this study found that profitability and leverage had a negative and significant effect on tax avoidance, liquidity has a positive and significant effect on tax avoidance, company size is unable to moderate the effect of profitability, leverage, liquidity on tax avoidance. The implication of this research is the importance of increasing profits or profitability which can make companies give a positive signal to the government throught paying taxes and not taking tax avoidance.